Fighting for America : The Struggle for Mastery in North America, 1519-1871 - Black, Jeremy, 1955- (Book collections on Project MUSE., 2011)
Prize winning author Jeremy Black traces the competition for control of North America from the landing of Spanish troops under HernÃn CortÃs in modern Mexico in 1519 to 1871 when, with the Treaty of Washington and the withdrawal of most British garrisons, Britain accepted American mastery in North America. In this wide-ranging narrative, Black makes clear that the process by which America gained supremacy was far from inevitable. The story Black tells is one of conflict, diplomacy, geopolitics, and poli.